The effect of parathyroidectomy on patients' symptoms in tertiary hyperparathyroidism. Issue 8 (7th April 2019) - See, Anna; Lim, Amy E. L.; Wong, Jiunn; Choong, Hui Lin; Iyer, N Gopalakrishna; Tan, Hiang Khoon; Tan, Ngian Chye; Ng, Jeremy C. F.
Abstract: Background: The efficacy of parathyroidectomy for primary and secondary hyperparathyroidism is well‐established but evidence in tertiary hyperparathyroidism is lacking. We examined parathyroidectomy's effect in tertiary hyperparathyroidism. Methods: Patients with tertiary hyperparathyroidism who underwent parathyroidectomy were followed up for 12 months. A modification of the 13‐item parathyroid symptoms list developed by Pasieka was administered at 0, 1, 3, 6, and 12 months post‐surgery. We also examined if preoperative factors would predict symptom improvement post‐surgery. Results: Ninety‐one patients were included. Survey response rates at 1, 3, 6, and 12 months post‐surgery were 97.8%, 90.1%, 82.4%, and 80.2%, respectively. Mean preoperative Pasieka parathyroid score (PSS) was 6.3 ± 2.7. At first month, PSS decreased to 2.9 ± 2.0 ( P < .001) and was sustained at 3, 6, and 12 months (2.7 ± 2.1, P < .001, 2.3 ± 1.6, P < .001 and 3.4 ± 2.5, P < .001). The degree of PSS reduction at 1‐month post‐parathyroidectomy correlated strongly with preoperative symptom severity (Pearson's coefficient: 0.690, P < .001). Conclusions: Parathyroid symptoms unequivocally improve post‐parathyroidectomy. The greatest degree of improvement was observed in early postoperative period up to 6 months.